Voluntary Nonfinancial Disclosure and the Cost of Equity Capital: The Initiation of Corporate Social Responsibility Reporting - Dhaliwal, Dan S.; Li, Oliver Zhen; Tsang, Albert; Yang, Yong George (The Accounting Review, 2011)
ABSTRACT: We examine a potential benefit associated with the initiation of voluntary disclosure of corporate social responsibility (CSR) activities: a reduction in firms’ cost of equity capital. We find that firms with a high cost of equity capital in the previous year tend to initiate disclosure of CSR activities in the current year and that initiating firms with superior social responsibility performance enjoy a subsequent reduction in the cost of equity capital. Further, initiating firms with superior social responsibility performance attract dedicated institutional investors and analyst coverage. Moreover, these analysts achieve lower absolute forecast errors and dispersion. Finally, we find that firms exploit the benefit of a lower cost of equity capital associated with the initiation of CSR disclosure. Initiating firms are more likely than non-initiating firms to raise equity capital following the initiations; among firms raising equity capital, initiating firms raise a significantly larger amount than do non-initiating firms.